Factors Associated With Self-Reported Concussion History in Middle School Athletes. (March 2020) - Terry, Douglas P.; Wojtowicz, Magdalena; Cook, Nathan E.; Maxwell, Bruce A.; Zafonte, Ross; Seifert, Tad; Silverberg, Noah D.; Berkner, Paul D.; Iverson, Grant L.
Abstract : Objective: Identifying personal characteristics associated with sustaining a concussion is of great interest, yet only a few have examined this in children. The purpose of this study was to examine the association between sex, neurodevelopmental disorders, health history, and lifetime history of self-reported concussion in 12- and 13-year-old athletes. Design: Cross-sectional study. Setting: Middle schools. Participants: Participants were 1744 twelve- and thirteen-year-old student athletes who completed preseason Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) testing, including a self-report questionnaire about previous concussions, developmental diagnoses, and previous medical treatment. Independent Variables: Age, sex, attention-deficit/hyperactivity disorder (ADHD), learning disabilities (LDs), and previous treatment for migraine. Main Outcome Measures: Self-reported history of concussion. Results: A minority of athletes (13.7%) reported previous concussions (1 concussion, n = 181; 2 concussions, n = 41; and 3+ concussions, n = 17). A small proportion reported a history of ADHD (4.4%), LD (2.8%) or migraine treatment (4.0%). Higher rates of self-reported previous concussions were associated with male sex [16.9% vs 9.1%; χ 2 (1) = 21.47, P < 0.001] and previous migraine treatment [31.9% vs 13.0%; χ 2 (1) = 20.08, P < 0.001]. There were no differences in self-reported concussion history between 12- and 13-year olds ( P = 0.18) and those with/without ADHD ( P = 0.41) or LDs ( P = 0.06). The overall logistic regression model was statistically significant [χ 2 (5) = 42.01, P < 0.001] but explained only 4.3% of the variance. Previous treatment for migraine [ P < 0.001, Exp(B) = 3.30] and male sex [ P < 0.001, Exp(B) = 2.06] were independently associated with a self-reported concussion history, whereas age, LD, and ADHD were not ( P 's > 0.05). Conclusions: Male sex and previous migraine treatment were associated with higher rates of self-reported previous concussions in both independent and multivariate models in middle school athletes, whereas age, ADHD, and LDs were not.